TREND OF MDR-TB IN KIRKUK- IRAQ-A 10 YEARS’ EXPERIENCE AND CHALLENGES (World Bulletin of Public Health, 2024)
Tuberculosis is still regarded as one of major public health burden worldwide, and the emergence of multi-drug resistant TB which is defined by resistance to both Isoniazid (INH) and Rifampicin (R) with or without resistance together drug; is adding problems to public health across the continents.(1),(2) The probable causes of increasing the prevalence of multi-drugs resistance (MDR) may be attributed to the emergence of human immunodeficiency virus (HIV), poverty, migration narcotic abuse and displacement following wars, finally the poor performance of National Tuberculosis Program Strategy (NTPS) may be one of the contributing factors, as irregular treatment is worse than no treatment of initial Tuberculosis (TB) cases.(3),(4) Iraq is one of Eastern Mediterranean Region Organization (EMRO) countries and it has intermediate to relatively high burden of TB rate (651100000).(3) Although drug resistance to antibiotics is a natural phenomenon, but in case of TB it is regarded as manmade, which is attributed to interrupted treatment and poor health serves, here, it is crucial to explore types of drug resistance to anti TB, actually two important patterns of drug resistance had rayed attention, they are the multidrug resistant (MDR) and extensively drug resistant (XDR). MDR being resistant to at least INH and Rifampicin, while (XDR) is defined as MDR TB with resistance to at least aflouroquinolone and one-second line injectable agent (amikacin, kanamycin and / or caprcomycin).(5),(6)
Keywords: MDR-TB; Kirkuk- Iraq